Impact of ZnO nanopriming on physiological and biochemical traits of wheat (Triticum aestivum L.) seedling - Priyanka Pandya; Sushil Kumar; Ghanshyam Patil; Monil Mankad; Zarna Shah (CABI Agriculture and Bioscience)
Abstract To ascertain the ideal dosage of ZnO NPs (Zinc Oxide Nanoparticles), we conducted an investigation on the priming effects of varying concentrations of ZnO NPs on germination and physio-biochemical parameters of wheat. In this study, ZnO NPs were synthesized and characterized for their physico-chemical properties followed by confirmation of the formation of ZnO NPs. Throughout this study, wheat seeds were subjected to ZnO NPs at various concentrations of 5, 50, 100, 250, and 500 ppm for a period of 4 h via continuous aeration. The primed seeds were sowed in plastic bags, allowed to grow for 21 days, following which comprehensive evaluations of physio-biochemical attributes were conducted. At 250 ppm, an impressive 100% of seeds successfully germinated compared to the control group. The examined physiological factors such as shoot length, root length, and fresh as well as dry weights of leaf and root tissues all exhibited notable increases with the ascending concentrations of ZnO NP up to 250 ppm. However, beyond this threshold, at 500 ppm, these parameters experienced a decline. Inductively coupled plasma atomic absorption spectrophotometer (ICP-AAS) measurements validated the progressive increase in Zinc content in the nanoprimed seedlings, further affirming the dose-dependent trend. Zinc oxide nanoparticles notably improved key biochemical features, including elevated levels of total chlorophyll, malondialdehyde (MDA), total protein, and the accumulation of osmolytes such as proline and glycine-betaine. Additionally, the presence of ZnO NPs led to increased activity of antioxidant enzymes like superoxide dismutase (SOD) and catalase in a dose-dependent mananer. Collectively, the amassed data underscores the efficacy of the 250 ppm ZnO NPs treatment, which emerged as superior in comparison to both the control group and other administered treatments. These findings underscore the potential of ZnO NPs at a concentration of 250 ppm as a valuable seed nanopriming agent, effectively enhanced germination and robust early-stage growth in young plants.